Review of relationship between dividend policy and price volatility - Qammar, Rabia; Ibrahim, Yusnidah; Alam, Md Mahmudul (Penerbit Akademia Baru, 2017)
This paper aims to focus on the relationship between dividend policy and stock price volatility through seminal literature on both theoretical and empirical evidences during 1989 to 2016. Based on the prior literature, this paper argued that the relationship between dividend policy and stock price volatility is inconsistent. Dividend policy is the most important element to measure the changes in stock prices. Furthermore, relationship between dividend policy and stock price volatility shows different results in developed and developing countries. The developed countries have more impact of this relationship as compared to developing countries. The various consequences of this relationship depend upon each country specific characteristics, different data sample and different methodology technique which utilized by researchers in developed and developing countries. This study describes empirical findings in both developed and developing countries. Most of the studies found negative relationship between dividend policy and stock price volatility along some controlled factors. Hence, this paper presented more updated and detailed review than previous studies.